Stereotypes and Risk Attitudes: Evidence from the Lab and the Field - Andrea Leuermann; Benjamin Roth (University of Heidelberg, Department of Economics, 2012)
Recent studies have found correlations between risk attitudes and several sociodemographic characteristics. In this paper, we deploy an artefactual fi eld experiment and study whether subjects - non-professionals and financial professionals - are aware of these correlations. This is largely confi rmed by our results for all subject groups. We show that the subjects attach informational value to sociodemographic information when assessing others' risk attitudes. This provides external validity to the correlations found between risk preferences and sociodemographics. A person's self-assessment of risk attitudes is the most helpful device for the subjects' assessments of others, although experienced professionals make use of it to a minor extent than all other subjects.
urn:nbn:de:bsz:16-opus-136301
Keywords: G02; D81; 330; Risk Preferences; Financial Advice; Artefactual Field Experiment; Behavioral Finance; Risikopräferenz; Finanzanalyse; Anlageverhalten; Sozialer Status; Feldforschung; Deutschland